O homem na estratégia de saúde da família - Marciel, Patricia Suerda de Oliveira (2009)
The research aimed to understand the general perception of men about their health care in a health unit família. This is an exploratory and descriptive qualitative approach, developed at the Center for Health Dr Vulpiano Cavalcante in the City of Parnamirim / RN. Participated in the investigation 12 men enrolled in the Estratégia de Saúde da Família ESF (Family Health Strategy), in the age-group 20 to 59 years lived in the catchment area of one of the ESF teams unit above. Data were collected from July to August 2009, through structured interviews, which, after transcription have undergone a process of identifying meaning units, coded and categorized according to the precepts of content analysis according to Bardin. Following in the footsteps of this method, originated the following themes: "Revealing what motivates men to seek assistance in the Estratégia de Saúde da Família," "Expressing knowledge of the Estratégia de Saúde da Família ", "an opinion about the care health and relationship with the ESF. The analysis was processed according to the principles of symbolic interactionism as Blumer. To support the discussions were used literary themes about man in the context of public health policies and the man in the family and the influences of gender. These, when they had their properties and dimensions analyzed, raised the central category Man on the Estratégia de Saúde da Família . The results show that respondents have limited knowledge about the ESF, your actions turn to use the service when no obligation arising from discomforts and accuracy of care. Moreover, delivering the opinion of the care with your health, even need, but recognizing that do not perform self-care. Given this reality, we can conclude that the perception of the man about his health in the ESF permeates gender issues that influence their behavior toward disease prevention and health promotion. This situation requires that the professionals and managers of health initiatives for the inclusion of man in the actions of the ESF assistance starting from the understanding of their conceptions of health care.